The effect of electromagnetic field (EMF) exposure on pericytes in brain tissues and blood oxidative stress level in rats - Syahirah Samsudin,; Yanti Rosli,; Asmah Hamid, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Studies on the potential effect of EMF exposure on permeability of the blood-brain barrier (BBB) in humans are virtually absent. This study was conducted to study the effect of EMF exposure on pericytes in brain tissues and its effect on oxidative stress level in the blood through total protein and malondialdehyde (MDA). About 16 male rats (Wistar) were used and divided into two groups which are negative control and treatment group. In negative control group, the animals were placed in a solenoid without any EMF exposure for 3 hours daily for 5 days. In the treatment group, the animals were placed in a solenoid with 0.3 mT EMF exposure for the same time duration. On day 3 and day 5, animals were sacrificed and the brain was removed for histological examination while on day 1, day 3 and day 5, the blood was collected for biochemistry analysis. Histological observation showed the presence of morphological changes in the brain tissues of rats that exposed to EMF. Statistical analysis showed that there is no significant decrease in total protein (p>0.05) between negative control group and treatment group. Meanwhile, MDA level in blood showed a significant increase in treatment group (p<0.05) as compared to the negative control group. The result obtained in this study, suggest that the exposure to EMF can cause changes to the morphology of pericytes in brain tissues, reduce the total protein level and also can increase the MDA level in blood of rats.